Pengolahan Empon-Empon Menjadi Minuman Kesehatan Berbasis Zero Waste Home Industry - Suci Fitriani Sammulia; Suhaera Suhaera; Delladari Mayefis; Sri Hainil (Lembaga Pengembangan Kinerja Dosen, 2021)
A collaborative project between lecturers and four students from the Mitra Bunda Health Institute around Tiban Baru, Batam City, successfully held outreach activities and distribution of empon-empon herbal medicine to 100 local residents from October 2020 to March 2021. Relying on local natural resources such as ginger, ginger , turmeric, and lemongrass leaves are rich in antioxidant compounds such as curcumin, gingerol, and phenol, this project aims to increase public health awareness and introduce herbal medicine empon-empon as a beneficial health alternative. The activity began with preparing materials and tools for making herbal medicine, then followed by material discussions and counseling with the community as well as a morning exercise event at the Tiban Baru Community Health Center as part of efforts to involve more people. In the process of making herbal medicine, community participation is very necessary, including adjusting the taste by adding enough brown sugar. This project succeeded in providing a positive impact by increasing local community health awareness while introducing holistic health values by utilizing local natural resources in a sustainable manner, as well as strengthening collaboration between educational institutions and the community in improving mutual health and welfare.